The p66shc-mediated Regulation of Hepatocyte Senescence Influences Hepatic Steatosis in Nonalcoholic Fatty Liver Disease - Zhang, Jing (Med Sci Monit, 2020)
BACKGROUND: Recent studies have suggested that hepatocyte senescence could contribute to hepatic steatosis and its progression in nonalcoholic fatty liver disease (NAFLD). However, the underlying mechanism causing hepatocyte senescence in this pathological condition is still unclear. A thorough understanding of the mechanism could provide a new target for therapeutic intervention. The purpose of this study was to investigate the role of p66shc in hepatocyte senescence and hepatocyte damage in NAFLD progression. MATERIAL/METHODS: We examined the expression levels of hepatic p66shc and senescence markers in rats and humans with NAFLD, and we assessed the effect of p66shc knockdown or overexpression on senescence and steatosis in human liver cells. RESULTS: In this study, we showed that increased hepatic p66shc expression was consistent with upregulated expression of the following senescence markers in NAFLD rats: heterochromatin protein-1-beta (HP1β), p16, p21, and p53. Furthermore, senescence and steatosis could be induced in hepatoblastoma cell line (HepG2) cells when cells were stimulated with a low concentration of H(2)O(2), and this effect was significantly alleviated by knockdown of p66shc. However, overexpression of p66shc could promote senescence and steatosis in L02 cells. Finally, increased hepatic p66shc protein levels correlated with enhanced expression of the senescence marker p21 and mirrored the degree of disease severity in NAFLD patients. CONCLUSIONS: Our findings indicated that the increase in hepatocyte senescence and steatosis in NAFLD may be caused by the upregulation of p66shc expression, implying that strategies for p66shc-mediated regulation of hepatocyte senescence may provide new therapeutic tools for NAFLD.